2009
DOI: 10.1264/jsme2.me09125
|View full text |Cite
|
Sign up to set email alerts
|

Nodulation-Dependent Communities of Culturable Bacterial Endophytes from Stems of Field-Grown Soybeans

Abstract: Endophytic bacteria (247 isolates) were randomly isolated from surface-sterilized stems of non-nodulated (Nod − ), wild-type nodulated (Nod + ), and hypernodulated (Nod ++ ) soybeans (Glycine max [L.] Merr) on three agar media (R2A, nutrient agar, and potato dextrose agar). Their diversity was compared on the basis of 16S rRNA gene sequences. The phylogenetic composition depended on the soybean nodulation phenotype, although diversity indexes were not correlated with nodulation phenotype. The most abundant phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 47 publications
5
22
0
Order By: Relevance
“…Okubo et al (2009) also reported similar results of the strong dominance Figure 3 Principal-coordinate analysis for the 16S ribosomal RNA (rRNA) gene clone libraries of soybean stem-associated bacteria in different nodulation phenotypes. The ordination was constructed using Unifrac distances weighted by the relative abundances.…”
Section: Discussionsupporting
confidence: 53%
“…Okubo et al (2009) also reported similar results of the strong dominance Figure 3 Principal-coordinate analysis for the 16S ribosomal RNA (rRNA) gene clone libraries of soybean stem-associated bacteria in different nodulation phenotypes. The ordination was constructed using Unifrac distances weighted by the relative abundances.…”
Section: Discussionsupporting
confidence: 53%
“…glycinea. These differences may reflect a bias in the culturability of leaf-associated bacterial communities (35,39). Alternatively, the bacterial cell enrichment method employed in the present study may have a bias regarding the efficiencies of cell extraction from plant tissues for different taxonomic groups.…”
Section: Discussionmentioning
confidence: 95%
“…1) clones (11,22,27,29,34,50,79,82,105,116,117,118) Clostridium magnum (GU129927.1) Clostridium sp. (AF281142.1) Uncultured Veillonellaceae (FJ393139.1) Uncultured Veillonellaceae (FJ393127.1) clones (6,13,17,19,32,36,37,39,47,49,56,59,67,71,74,80,85,93,94,99,100,106,107,108,111,112,120) clones (7,8,18,21,30,31,38,43,46,86,95,103,119) Sporolactobacillus laevolacticus (AB362643.1) clones (54,63,66,…”
mentioning
confidence: 99%